2005
DOI: 10.1074/jbc.m410140200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties and Metabolic Contributions of Yeast Mitochondrial and Cytosolic NADP+-specific Isocitrate Dehydrogenases

Abstract: To compare kinetic properties of homologous isozymes of NADP ؉ -specific isocitrate dehydrogenase, histidine-tagged forms of yeast mitochondrial (IDP1) and cytosolic (IDP2) enzymes were expressed and purified. The isozymes were found to share similar apparent affinities for cofactors. However, with respect to isocitrate, IDP1 had an apparent K m value ϳ7-fold lower than that of IDP2, whereas, with respect to ␣-ketoglutarate, IDP2 had an apparent K m value ϳ10-fold lower than that of IDP1. Similar K m values fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 48 publications
(50 reference statements)
3
38
0
Order By: Relevance
“…Han et al (9) reported that sublethal whole-body irradiation marginally increased the expression of MnSOD mRNA and protein in mice spleens but significantly decreased catalase and CuZnSOD activity. In this study, the authors suggested that MnSOD played an important role in radiation-induced cellular damage and that the increase in MnSOD activity may be used as a rapid predictive assay of radiosensitivity in the clinical setting (31).…”
Section: Discussionmentioning
confidence: 99%
“…Han et al (9) reported that sublethal whole-body irradiation marginally increased the expression of MnSOD mRNA and protein in mice spleens but significantly decreased catalase and CuZnSOD activity. In this study, the authors suggested that MnSOD played an important role in radiation-induced cellular damage and that the increase in MnSOD activity may be used as a rapid predictive assay of radiosensitivity in the clinical setting (31).…”
Section: Discussionmentioning
confidence: 99%
“…3 and Table 3). Lack of one of the two isoforms of the NAD + -dependent isocitrate dehydrogenase in the idh2D strain, and lack of one of the three isoforms of the NADP + -dependent isocitrate dehydrogenase in the idp1D strain, produced significantly lower 2-OG contents [32,33] (Fig. 3 and Table 3).…”
Section: Metabolite Contents and Fluxesmentioning
confidence: 99%
“…For 2-OG extraction and intracellular content determination, 100 mL of cell culture at an attenuance at 600 nm of 2.0 were harvested by rapid centrifugation and extracted in boiling water as previously described [33]. Determination of Lys incorporated into proteins (Lys prot ) was performed as follows.…”
Section: Metabolite Determination and Analysismentioning
confidence: 99%
“…15) However, in A. niger, the alterations in the specific activity of NADP + -ICDH, but not NAD + -ICDH, are related to the extremely high production of citric acid. 25,[27][28][29] In addition, neither the gene expression nor the enzymatic activity of NAD + -ICDH are affected by the increases in the transcript level of the NADP + -ICDH gene and the specific activity of its product.…”
Section: Discussionmentioning
confidence: 99%
“…Idp1p contains mitochondrial targeting signal peptides in its N-terminus, 11) Idp3p contains peroxisomal targeting signal peptides in its C-terminus, 12,13) and Idp2p contains no targeting signal peptides and is localized in the cytoplasm. 14) Because intracellular concentrations of citric acid and α-ketoglutaric acid in idp2 disruptants are markedly lower than those in idp1 disruptants, 15) mitochondrial NADP + -ICDH (Idp1p) may play a minor role in supplying α-ketoglutaric acid via the TCA cycle compared to mitochondrial NAD + -ICDH. Codisruption of idp2 in idh2 disruptants results in glutamate auxotrophy, indicating that cytosolic NADP + -ICDH (Idp2p) contributes to the synthesis of glutamic acid.…”
mentioning
confidence: 99%